The influence of verbal ability and social intelligence on students’ self-efficacy - Huang, Billy (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to determine the influence of verbal ability and social intelligence on the self-efficacy of students at SMP Metta Maitreya Pekanbaru. The research employed a quantitative approach using a survey method. The sample consisted of 183 students selected through simple random sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using simple and multiple linear regression. The results showed that verbal ability had a significant influence on students' self-efficacy with a coefficient of determination R² = 0.402 and a t-value of 11.031. Social intelligence also had a significant effect on self-efficacy with R² = 0.693 and t = 20.206. Simultaneously, verbal ability and social intelligence had a meaningful effect on self-efficacy with R² = 0.711 and an F-value of 221.009. These findings indicate that social intelligence is the dominant factor in enhancing students' self-efficacy.